Image Analysis of Circulating Tumor Cells and Leukocytes Predicts Survival and Metastatic Pattern in Breast Cancer Patients - Da Col, Giacomo; Del Ben, Fabio; Bulfoni, Michela; Turetta, Matteo; Gerratana, Lorenzo; Bertozzi, Serena; Beltrami, Antonio Paolo; Cesselli, Daniela (Frontiers in Oncology, 2022)
Background The purpose of the present work was to test whether quantitative image analysis of circulating cells can provide useful clinical information targeting bone metastasis (BM) and overall survival (OS > 30 months) in metastatic breast cancer. Methods Starting from cell images of epithelial circulating tumor cells (eCTC) and leukocytes (CD45pos) obtained with DEPArray, we identified the most significant features and applied single-variable and multi-variable methods, screening all combinations of four machine-learning approaches (Naïve Bayes, Logistic regression, Decision Trees, Random Forest). Results Best predictive features were circularity (OS) and diameter (BM), in both eCTC and CD45pos. Median difference in OS was 15 vs. 43 (months), p=0.03 for eCTC and 19 vs. 36, p=0.16 for CD45pos. Prediction for BM showed low accuracy (64%, 53%) but strong positive predictive value PPV (79%, 91%) for eCTC and CD45, respectively. Best machine learning model was Naïve Bayes, showing 46 vs 11 (months), p<0.0001 for eCTC; 12.5 vs. 45, p=0.0004 for CD45pos and 11 vs. 45, p=0.0003 for eCTC+CD45pos. BM prediction reached 91% accuracy with eCTC, 84% with CD45pos and 91% with combined model. Conclusions Quantitative image analysis and machine learning models were effective methods to predict survival and metastatic pattern, with both eCTC and CD45pos containing significant and complementary information.